PENGARUH EARNING PER SHARE (EPS), UKURAN PERUSAHAAN, PROFITABILITAS, DAN LEVERAGE TERHADAP NILAI PERUSAHAAN (Studi Kasus Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2009-2011) - Sukma Mindra; Teguh Erawati (Jurnal Akuntansi, 2014)
This study discusses the value of the company and financial ratios based on financial statements of listed companies in Indonesia Stock Exchange during the period 2009-2011. The purpose of this research is to determine whether the Earning Per Share (EPS), Company Size, Profitability and Leverage have an influence on company value. This study was built with five hypotheses, namely (1) Earning Per Share (EPS) has a positive effect on company value. (2) Company size has a positive impact on company value. (3) Profitability has a positive effect on company value. (4) Leverage has a negative effect on company value. The type of data in this study is secondary data. The samples in this study using purposive sampling method and method polled. Companies sampled as many as 45 of the 136 companies listed on the Indonesia Stock Exchange during the period 2009-2011. This research is quantitative, and statistical testing using multiple linear regression. By using regression analysis, it can be seen that the variable Earning Per Share (EPS), Company Size, Profitability and Leverage simultaneously have a significant influence on firm value. Partial test results, Firm Size and Profitability positive and significant impact on company value. Earning Per Share (EPS) and Leverage has a negative and significant impact on company value. Keywords: Earning Per Share (EPS), Company Size, Profitability, Leverage, Corporate Value.